Culture-Based Learning Model for Speaking Skills (Maharat al kalam) in Islamic Boarding Schools - Wahyudin Wahyudin (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2025)
The instruction of maharat al-kalam (speaking skills) in Arabic often faces significant challenges due to the lack of cultural integration, which hampers students’ ability to grasp authentic communicative contexts. This study investigates a culturally integrated instructional model implemented at Ar-Rayah Islamic Boarding School in Sukabumi and examines its contribution to enhancing students’ Arabic speaking proficiency. Employing a qualitative approach through a case study design, data were collected via interviews, observations, and document analysis, and subsequently analyzed using the interactive model of Miles and Huberman. The findings reveal that maharat al-kalam instruction at Ar-Rayah adopts a culturally grounded approach, utilizing the latest eight-volume edition of Al-'Arabiyyah Bayna Yadayk as core material, supplemented by various additional resources. The instructional strategy encompasses curriculum development, optimized dormitory-based learning activities, extended instructional hours, Arab cultural immersion, intensive language reinforcement programs, and engagement with native Arabic speakers. Learning media include audio, visual, and audiovisual resources delivered both online and offline. This integrative and immersive approach has proven effective in fostering communicative competence by creating a more contextualized and interactive learning environment.